2007
DOI: 10.1097/ss.0b013e3180577270
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Desorption Kinetics in Relation to Phosphorus Forms and Sorption Properties of Portuguese Acid Soils

Abstract: While much information exists on the quantitative relationships between phosphorus (P) sorption and soil properties, comparatively less attention has been given to the influence of soil properties and P forms on the kinetics of P desorption, and to the relationships between desorbable and sorbed P. The aim of this study was to rationalize

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(12 citation statements)
references
References 25 publications
3
9
0
Order By: Relevance
“…This result was in agreement with our initial hypothesis and with the results of other studies on acidic soils (Börling et al 2004;do Carmo Horta and Torrent 2007;Villapando and Graetz 2001). Particularly, the m and n parameters, which describe the immediate and slow physical-chemical reactions at the solid-to-solution interface, were better correlated with the poorly crystalline fractions ("ox" method) than with the crystallized fractions ("cdb" minus the "ox" method; Walbridge et al 1991), suggesting that the poorly crystalline fractions were the most reactive.…”
Section: Al and Fe Oxides And Soil Organic Mattersupporting
confidence: 95%
See 1 more Smart Citation
“…This result was in agreement with our initial hypothesis and with the results of other studies on acidic soils (Börling et al 2004;do Carmo Horta and Torrent 2007;Villapando and Graetz 2001). Particularly, the m and n parameters, which describe the immediate and slow physical-chemical reactions at the solid-to-solution interface, were better correlated with the poorly crystalline fractions ("ox" method) than with the crystallized fractions ("cdb" minus the "ox" method; Walbridge et al 1991), suggesting that the poorly crystalline fractions were the most reactive.…”
Section: Al and Fe Oxides And Soil Organic Mattersupporting
confidence: 95%
“…In acidic soils, the iP sorption capacity was found to be mainly correlated with Al and Fe oxides (Börling et al 2004;Daly et al 2001;do Carmo Horta and Torrent 2007;Maguire et al 2001;Singh and Gilkes 1991;Villapando and Graetz 2001), organic matter (Daly et al 2001;Dubus and Becquer 2001), or clay (Börling et al 2004;Singh and Gilkes 1991). Soil physical-chemical properties were consequently used to build pedotransfer functions to predict the iP sorption capacity (Borggaard et al 2004;Burkitt et al 2006;Villapando and Graetz 2001).…”
Section: Introductionmentioning
confidence: 98%
“…soil properties were similar in magnitude to those of molybdate, but with an opposite sign. The results for phosphate are in line with previous measurements of the kinetics of phosphate sorption and release (García-Rodeja and Gil-Sotres, 1997; Zeng et al, 2003;do Carmo Horta and Torrent, 2007).…”
Section: Kinetic Constants From the Elovich Equationsupporting
confidence: 81%
“…Similar results were obtained by Zeng et al (2003) for the sorption of phosphate by two Andisols. The same pattern was observed for the sorption of molybdate and phosphate by Al-and Fehydroxides, goethite, and acid soils (Bolan et al, 1985;Zhang and Sparks, 1989;Freese et al, 1995;Barrow, 1999;Brinton and O'Connor, 2003;do Carmo Horta and Torrent, 2007). Barrow (1999) has suggested that the "slow" reaction is due to diffusion of sorbed anions from surface sites into micropores within the structure of the soil constituents.…”
Section: Sorption Kineticsmentioning
confidence: 52%
“…Parameter n, which accounts for the slow physical-chemical reactions, was extremely low (0.009), while the maximum theoretical value is 0.5 (Fardeau et al, 1991). The small number of active exchange sites on the solid constituents inferred by both the low Psorbing capacity and the low isotopic exchanges is probably explained by the low amorphous Al and Fe oxide contents in our acidic sandy soil (Chen et al, 2003;do Carmo Horta and Torrent, 2007). The amount of amorphous Al plus Fe was only 7.4 · 10 -6 mol g −1 whereas it can reach 0.5-1 · 10 −3 mol g −1 (McDowell and Condron, 2000;Stroia et al, 2007).…”
Section: Is the Methods Applicable For A Wide Variety Of Soil Conditions?mentioning
confidence: 92%